X-ray photoelectron spectroscopy analysis of nafion® 117 electrolytic membrane - Amir H. Khadum; Wan Ramli Wan Daud; Abu Bakar Mohamad; Mohammad H. Rasheed; Ambar Yarmo (Universiti Kebangsaan Malaysia, 2000)
A study of elemental and chemical composition of Nafion® 117 electrolytic surface was conducted using X-ray photoelectron spectroscopy. The major chemical compositions of the membrane surface were mainly fluorine, carbon, oxygen, sulphur and titanium with mass concentration percentage of 60.22, 24.54, 11.52, 2.40 and 1.32, respectively. The curve fitting for carbon spectrum indicates three C-F namely, F2-C, F-C and F3-C chemical environments; two types of oxygen chemical environments, O3-S and CF-O-CF2. In addition, one type of fluorine environment; one type of sulphur environment, S-O3 and one type of titanium environment, Ti-O are found on the surface of the membrane.